Implementing knowledge discovery in enhancing university student services portfolio management in higher education institutions - PAULINO H. GATPANDAN; SHANETH C. AMBAT (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The Student Welfare and Formation Office (SWAFO) of De La Salle University-Dasmarinas, Philippines, used Classification Techniques and Data Envelopment Analysis to analyze student demographics and disciplinary infractions. This paper describes how Knowledge Discovery was used to improve the management of the university’s portfolio of student services.Methodology: To identify the effective Decision-Making Unit (DMU) attributed to colleges, the Data Envelopment Analysis was used. The correlation between student demographics and offending behavior was analyzed using the CHAID algorithm.Findings: The CHAID algorithm is implemented in a software application that is designed to be a predictive analytical software application that predicts student offenses, and a remediation plan is developed as a result. The SWAFO staff and five (5) IT professionals evaluate the software.Implications/Novelty: This research will help SWAFO’s process improvement initiative and delve deeper into the change by utilizing the remediation system plan. This work adds to our understanding of DEA and the design of remediation systems in higher education.